Amination and formation of sp2 C-N Bonds - Ma, Dawei (Topics in Organometallic Chemistry,, 2013)
Georgia S. Lemen and John P. Wolfe: Palladium-Catalyzed sp2C-N Bond Forming Reactions: Recent Developments and Applications.- Arkaitz Correa and Carsten Bolm: Metal-catalyzed C(sp2)-N bond formation.- Yongwen Jiang and Dawei Ma: Assembly of N-containing heterocycles via Pd and Cu-catalyzed C-N bond formation reactions.- Mannepalli Lakshmi Kantam, Venkat Reddy Chintareddy, P. Srinivas, Suresh Bhargava: Recent Developments in Recyclable Copper Catalyst Systems for C−N Bond Forming Cross-Coupling Reactions Using Aryl Halides and Arylboronic Acids.- Florian Monnier and Marc Taillefer: Copper-Catalyzed C(aryl)-N Bond Formation.